2009
DOI: 10.1021/ja807219x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structural Characterization, and Unusual Field-Effect Behavior of Organic Transistor Semiconductor Oligomers: Inferiority of Oxadiazole Compared with Other Electron-Withdrawing Subunits

Abstract: A new series of heterocyclic oligomers based on the 1,3,4-oxadiazole ring were synthesized. Other electron-deficient cores (fluorenone and fumaronitrile) were introduced to investigate the oligomers as n-channel materials. The physical properties, thin film morphologies, and field-effect transistor characteristics of the oligomers were evaluated. Thin films were deposited at different substrate temperatures and on variously coated Si/SiO(2) for device optimization. Contrary to our expectations, the thin film d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(44 citation statements)
references
References 99 publications
1
43
0
Order By: Relevance
“…Transition metal-catalysed cross-coupling reactions, such as Stille, Suzuki etc. are typically used for the formation of thiophene–thiophene or azole–thiophene bonds [14,1617]. However, the best results (higher yields, more facile purification, shorter reaction times) are obtained by the formation of the azole ring via appropriately functionalized bithiophenes [14,22].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Transition metal-catalysed cross-coupling reactions, such as Stille, Suzuki etc. are typically used for the formation of thiophene–thiophene or azole–thiophene bonds [14,1617]. However, the best results (higher yields, more facile purification, shorter reaction times) are obtained by the formation of the azole ring via appropriately functionalized bithiophenes [14,22].…”
Section: Resultsmentioning
confidence: 99%
“…One of the possible ways of the preparation of low molecular mass semiconductors, showing higher than oligothiophene IP values, is to synthesize molecules in which a central electron accepting group separates two bi-, ter- or quaterthiophene units. Such compounds containing thiadiazole [1015], oxadiazole [1417] or tetrazine units [13,1820] have been reported. Moreover, luminescence properties of these derivatives are superior to those of the corresponding penta-ring oligothiophenes.…”
Section: Introductionmentioning
confidence: 99%
“…[19] Keywords: 1,2-dicyanoethene ·diarylethenes · molecular switches ·p hotochromism ·photoisomerization Its two isomers exhibit significantly different molecular geometries leading to highly contrasting coplanarities, effective conjugations,molecular dipole moments,end-to-end distances,a nd symmetries.S pectral studies on pure isomers showed al arge separation between their l max and avariation in their relative absorption strengths.A sar esult, 4TCE can be efficiently switched between its cis and trans forms by irradiating with blue and white light, such that it is au seful photoswitch with manageable photoisomerization, high con- Angewandte version efficiency, and no requirement of aU Vl ight trigger.…”
Section: Methodsmentioning
confidence: 99%
“…The 1,3,4-oxadiazole derivatives have been widely studied as materials in electroluminescent (EL) devices due to their electron deficiency, high thermal and oxidative stability [6][7][8][9][10][11]. Furthermore, oxadiazole-based oligomers with electron-accepting end moieties have also been applied in organic field-effect transistors (OFETs) [12,13]. In recent years, many 1,3,4-oxadiazole derivatives have been widely used as electrontransporting materials.…”
Section: Introductionmentioning
confidence: 99%